2018
DOI: 10.1016/j.bonr.2018.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics-based profiles predictive of low bone mass in menopausal women

Abstract: Osteoporosis is a skeletal disorder characterized by compromised bone strength and increased risk of fracture. Low bone mass and/or pre-existing bone fragility fractures serve as diagnostic criteria in deciding when to start medication for osteoporosis. Although osteoporosis is a metabolic disorder, metabolic markers to predict reduced bone mass are unknown. Here, we show serum metabolomics profiles of women grouped as pre-menopausal with normal bone mineral density (BMD) (normal estrogen and normal BMD; NN), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
38
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 45 publications
7
38
0
Order By: Relevance
“…In line with the findings of animal studies, human studies also highlight the importance of amino acid and lipid metabolism in bone. In particular, many amino acids were reported to be associated with BMD by multiple independent studies [105][106][107][108][109] . For example, glutamine is increased 107,110 and proline is decreased in menopausal women with decreased BMD 109 .…”
Section: Metabolomicsmentioning
confidence: 99%
See 1 more Smart Citation
“…In line with the findings of animal studies, human studies also highlight the importance of amino acid and lipid metabolism in bone. In particular, many amino acids were reported to be associated with BMD by multiple independent studies [105][106][107][108][109] . For example, glutamine is increased 107,110 and proline is decreased in menopausal women with decreased BMD 109 .…”
Section: Metabolomicsmentioning
confidence: 99%
“…For example, glutamine is increased 107,110 and proline is decreased in menopausal women with decreased BMD 109 . Moreover, carbohydrate 108 and nucleoside 106 metabolism are also altered in women with decreased BMD. Finally, BMD-related metabolic pathways have been reported, including bile acid biosynthesis, which might affect intestinal calcium absorption 107 , and the tricarboxylic acid cycle, which might be related to increased oxidative stress in patients with low BMD 108 .…”
Section: Metabolomicsmentioning
confidence: 99%
“…Previous metabolomics-based studies have reported associations with amino acids and assessments of bone health [ 28 , 29 , 30 ]. Additional work has linked the intake of alanine, arginine, glutamic acid, and proline to a higher BMD at the spine and forearm in a cross-sectional study of females aged 18 to 79 years [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Predictive metabolomics-At one extreme of the predictive use of metabolomics is research that looks at metabolomic profiles in children (e.g.,-children who were breast-fed versus those that were not) [108], to determine if there is a signature present at a young age that could be used to predict some later aspect of health and development. The reports of prospective use of these kinds are markers are varied in scope, but a small sampling of the literature finds studies that indicate that there are also signatures that contain predictive markers of the progression of amyotrophic lateral sclerosis [109], bone mass in menopausal women [110] and a proclivity towards the development of major depression [87]. Of perhaps great relevance given the coronavirus pandemic is the finding that predictions about susceptibility to acute respiratory distress syndrome (ARDS) might also be made using metabolomic markers [111].…”
Section: Procedural Testingmentioning
confidence: 99%